EFFICACY OF CERTAIN BIO AGENTAS AND FUNGICIDES AGAINST ROOT ROT OF CHILLI (CAPSICUM ANNUM L.) - MALTI DEVI PATEL; ABHILASHA A. LAL; PRABHAT PAL SINGH (The Bioscan, 2014)
The present study was carried out with objective to evaluate the efficacy of bio-agents viz. Trichoderma viride @ 2%, Pseudomonas fluorescens @ 2%, T. harzianum @ 2% and fungicides viz. copper oxy chloride @ 0.1%, carbendazim @ 0.1%, captan @ 0.3% against R. solani under in-vitro condition by dual culture and poisoned food techniques. The experiment was laid out in a complete randomized block design with six treatments and five replications. All the bio-agents and fungicides were evaluated singly. All the treatments significantly inhibited the mycelial growth of R. solani as compared to control. Copper oxy chloride was the best treatment which inhibited 94.44 percent mycelial growth of R. solani followed by carbendazim (93.78), captan (92.22), T. viride (87.22 %), P. fluorescens (85.56 %) and T. harzianum (82.22 %). In-situ (field and pot culture) experiments were carried out in randomized block design with six treatments and three replications. Copper oxy chloride was found to be the most effective treatment and recorded minimum disease incidence (11.11 %) and better yield (73.12 q/ha) followed by T. viride @ 2%, P. fluorescens @ 2%, T. harzianum @ 2%, carbendazim @ 0.1%, and captan @ 0.3% .Use of T. viride recorded maximum plant height (23.93 cm and 48.60 cm at 45 and 90 DAT, respectively).